Snakebite in children: a two year retrospective review of victims admitted to a tertiary care hospital in sri lanka - Jayasinghe, Y.C.; Kasturiratne, A.; Rajindrajith, S.; Samaraweera, S.A.S.G.; de Silva, H.J. (Sri Lanka College of Paediatricians, 2010)
INTRODUCTION: Snakebite is an incident which causes great parental concern and medical unease, and envenomation is always more serious in a child. OBJECTIVE: To determine the pattern and characteristics of snake bites in children admitted to a tertiary care hospital in Southwest Sri Lanka. DESIGN, SETTING AND METHOD: A retrospective descriptive study was conducted to collect data on circumstances of the bite, clinical manifestations and management of paediatric victims of snakebite. Patient records of children admitted to the paediatric wards of Colombo North Teaching Hospital, Ragama, from January 2008 to December 2009 were reviewed. RESULTS: Our study population comprised 41 children (1.6 per 1000 admissions). Malerfemale ratio was 23:18. Mean age was 6 (SD=3.46) years. The bites were definite in 4 subjects and circumstantial (fang marks, signs of local and systemic envenomation) in the others. Twenty five (61%) were between 5 to 12 years of age. Nine (22%) bites occurred indoors and 13 (31.7%) in the home garden. In 12 (29.3%) the place of bite was not documented. In 42% the bite took place between 4pm-8pm. The snake species was identified by carers in 19 (46%) and confirmed by a doctor in 16 (39%) by identifying the dead snake. Of the 16 snakes brought for identification., 8 were hump-nosed vipers, 2 were Russell vipers, one was a krait and the rest were non-venomous species. Definite puncture marks were seen in 17 (41.4%) and were on the lower limbs in 11 (26.8%) and on the upper limbs in 6 (14.6%). First aid was given to 12 (29%) of the victims and the median time taken to reach hospital was 30 minutes (range 10 minutes to 15 hours). Nephrotoxicity developed in 1 (2.4%) (Russell viper bite). Antivenom was required by only 4 children in whom Russell viper bite was either suspected or confirmed. Three children developed reactions to antivenom. There were no deaths. None required intensive care. The median stay in hospital was 1 day (range 1-5 days) with 35 (94.6%) children being discharged home within 2 days. CONCLUSIONS: Snakebite in children was mainly diagnosed on circumstantial evidence, and mostly occurred in and around their homes. The outcome was good in all patients probably because the hump-nosed viper or non-venomous snakes were the offenders in most cases in this study.
Abstract of Poster Presentation (PP 02) - The 13th Annual Scientific Congress of the Sri Lanka College of Paediatricians, 28th-31st of July, 2010, Waters Edge, Battaramulla
Keywords: Snake Bites; Retrospective Studies; Child